How Couple’s Relationship Lasts Over Time? A Model for Marital Satisfaction - Abreu-Afonso, J. (2021)
High rates of divorce seem related to low marital satisfaction levels; however, there is still a lack of a model that can help understand the couple’s resilience and fragility throughout the life cycle. This research explores the role of communication patterns, their own and partner’s motivation for conjugality, cohesion and flexibility within a couple, and several sociodemographic characteristics (e.g., stage of the family life cycle) that can explain marital satisfaction. A sample of 331 Portuguese in a marital relationship completed a sociodemographic questionnaire and marital satisfaction measures, communication and conflict management competencies, cohesion and flexibility, and motivation. Adequate statistical analysis was performed using descriptive statistics and structural equation modeling. Both measurement and structural model performed in the study presented a good fit, with five significant predictors of marital satisfaction (that accounted for 85% of the variability): intrinsic motivation (b ¼ .64), communication (b ¼ .31), families with young children (b ¼ .08), families with teenagers (b ¼ .07) and professional/academic status (b ¼ .06). By identifying a model for marital satisfaction, this research provides clues regarding which aspects might need to be considered in couples’ clinical work to promote healthier relationships.